Development of Learning Modules Discovery Learning Models Based on Results of Plant Identification in School Environments - Shofiyati, Aida; Retnoningsih, Amin; Ridlo, Saiful (Journal of Innovative Science Education, 2019)
The school environment has potential as a learning resource for developing contextual teaching materials. The purpose of this study is to test the validity and effectiveness of the module learning Discovery Learning model based on identification of plant in SMAN 1 Bangsri, Jepara, Central Java. This research is a development research consist of plants identification and module development. The plants identification refer to internet and book. Module development refers to Sugiyono's model and its validity assessed by 4 validators. The effectiveness of module tested by pretest-posttest control group design. The sample class taken by cluster random sampling technique, 1 experiment class and 1 control class. There are 147 species plant in SMAN 1 Bangsri, they are member of divisio Bryophyta, Pteridophyta, and Spermatophyta. The content of module is a valid, presentation and graphics, and language are a very valid. The result of cognitive test significantly different between control and experiment class. The affective value which very good predicate in the experiment class higher than the control class, while the psychomotor value only a slight difference. The results of validity test and effectiveness of module Discovery Learning model based on the results of plants identification are feasible as teaching materials.